The Perils of Navigating Activity-Dependent Alternative Splicing of Neurexins - Liakath-Ali, Kif; Südhof, Thomas C. (Frontiers in Molecular Neuroscience, 2021)
Neurexins are presynaptic cell-adhesion molecules essential for synaptic function that are expressed in thousands of alternatively spliced isoforms. Recent studies suggested that alternative splicing at splice site 4 (SS4) of Nrxn1 is tightly regulated by an activity-dependent mechanism. Given that Nrxn1 alternative splicing at SS4 controls NMDA-receptor-mediated synaptic responses, activity-dependent SS4 alternative splicing would suggest a new synaptic plasticity mechanism. However, conflicting results confound the assessment of neurexin alternative splicing, prompting us to re-evaluate this issue. We find that in cortical cultures, membrane depolarization by elevated extracellular K+-concentrations produced an apparent shift in Nrxn1-SS4 alternative splicing by inducing neuronal but not astroglial cell death, resulting in persistent astroglial Nrxn1-SS4+ expression and decreased neuronal Nrxn1-SS4– expression. in vivo, systemic kainate-induced activation of neurons in the hippocampus produced no changes in Nrxn1-SS4 alternative splicing. Moreover, focal kainate injections into the mouse cerebellum induced small changes in Nrxn1-SS4 alternative splicing that, however, were associated with large decreases in Nrxn1 expression and widespread DNA damage. Our results suggest that although Nrxn1-SS4 alternative splicing may represent a mechanism of activity-dependent synaptic plasticity, common procedures for testing this hypothesis are prone to artifacts, and more sophisticated approaches will be necessary to test this important question.